Agreement between Fiber Optic and Optoelectronic Systems for Quantifying Sagittal Plane Spinal Curvature in Sitting - Cloud, Beth A. (2014)
Spinal posture affects how individuals function from a manual wheelchair. There is a need to directly quantify spinal posture in this population to ultimately improve function. A fiber optic system, comprised of an attached series of sensors, is promising for measuring large regions of the spine in individuals sitting in a wheelchair. The purpose of this study was to determine the agreement between fiber optic and optoelectronic systems for measuring spinal curvature, and describe the range of sagittal plane spinal curvatures in natural sitting. Able-bodied adults (n=26, 13 male) participated. Each participant assumed three sitting postures: natural, slouched (accentuated kyphosis), and extension (accentuated lordosis) sitting. Fiber optic (ShapeTape) and optoelectronic (Optotrak) systems were applied to the skin over spinous processes from S1 to C7 and used to measure sagittal plane spinal curvature. Regions of kyphosis and lordosis were identified. A Cobb angle-like method was used to quantify lordosis and kyphosis. Generalized linear model and Bland-Altman analyses were used to assess agreement. A strong correlation exists between curvature values obtained with Optotrak and ShapeTape (R(2)=0.98). The mean difference between Optotrak and ShapeTape for kyphosis in natural, extension, and slouched postures was 4.30° (95%LOA: −3.43-12.04°), 3.64° (95%LOA: −1.07-8.36°), and 4.02° (95%LOA: −2.80-10.84°), respectively. The mean difference for lordosis, when present, in natural and extension postures is 2.86° (95%LOA: −1.18-6.90°) and 2.55° (95%LOA: −3.38-8.48°), respectively. In natural sitting, the mean±SD of kyphosis values was 35.07± 6.75°. Lordosis was detected in 8/26 participants: 11.72±7.32°. The fiber optic and optoelectronic systems demonstrate acceptable agreement for measuring sagittal plane thoracolumbar spinal curvature.